Unfolding the moving-in experiences of international students at a Malaysian private tertiary institution / Shariffah Bahyah Syed Ahmad and Siow Heng Loke - Syed Ahmad, Shariffah Bahyah; Siow, Heng Loke (Universiti Teknologi MARA, 2022)
This paper focuses on the experience of international undergraduate students as they move into a university environment. Utilising a phenomenological approach with Schlossberg’s Theory of Transition as the framework, data was collected through semi-structured interviews with 19 undergraduate students, all enrolled in one private university. The study found that their moving-in experiences were influenced by their aspirations, feelings and expectations. Conflicting emotions accompanied their departure from their home country: sorrow and anxiety versus excitement for their new life. Aided by a relatively smooth immigration process, the students moved on to experience memorable moments where friendships were formed and exploration of the surrounding areas was acculturated. Challenges faced include those of physical nature (weather and food), academic, and perhaps the most serious of which, psychosocial: in the form of homesickness and feeling of foreignness.